CoVaccine HT™ Adjuvant Potentiates Robust Immune Responses to Recombinant SARS-CoV-2 Spike S1 Immunization - Haun, Brien K.; Lai, Chih-Yun; Williams, Caitlin A.; Wong, Teri Ann S.; Lieberman, Michael M.; Pessaint, Laurent; Andersen, Hanne; Lehrer, Axel T. (Frontiers in Immunology, 2020)
The current COVID-19 pandemic has claimed hundreds of thousands of lives and its causative agent, SARS-CoV-2, has infected millions, globally. The highly contagious nature of this respiratory virus has spurred massive global efforts to develop vaccines at record speeds. In addition to enhanced immunogen delivery, adjuvants may greatly impact protective efficacy of a SARS-CoV-2 vaccine. To investigate adjuvant suitability, we formulated protein subunit vaccines consisting of the recombinant S1 domain of SARS-CoV-2 Spike protein alone or in combination with either CoVaccine HTTM or Alhydrogel. CoVaccine HTTM induced high titres of antigen-binding IgG after a single dose, facilitated affinity maturation and class switching to a greater extent than Alhydrogel and elicited potent cell-mediated immunity as well as virus neutralising antibody titres. Data presented here suggests that adjuvantation with CoVaccine HTTM can rapidly induce a comprehensive and protective immune response to SARS-CoV-2.